2016
DOI: 10.1002/jhet.2588
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Antioxidant Activity of Some New Thiazolyl–Pyrazolone Derivatives

Abstract: 3‐Methyl‐1‐thiocarbamoyl‐2‐pyrazolin‐5‐one has been utilized as a core for the synthesis of some 1‐(thiazol‐2‐yl)‐pyrazolin‐5‐one derivatives through diazo‐coupling reaction and/or Knoevenagel condensation followed by heterocyclization with some α‐halogenated reagents such as bromoacetone, phenacyl bromide, and ethyl bromoacetate. Base prompted addition of the core compound to an equimolar amount of phenyl isothiocyanate furnished 3‐methyl‐4‐phenylthiocarbamoyl‐1‐thiocarbamoyl‐2‐pyrazolin‐5‐one which undergoes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(19 citation statements)
references
References 21 publications
0
19
0
Order By: Relevance
“…Gaffer and co-workers [106] screened the antioxidant activity of a cluster of thiazolyl-pyrazolone derivatives through 2, 2 0 -azinobis(3-ethylbenzothiazoline-6-sulphonic acid) (ABTS) radical cation decolorization assay. Compounds 149 and 150 ( Fig.…”
Section: Antioxidant Agentsmentioning
confidence: 99%
“…Gaffer and co-workers [106] screened the antioxidant activity of a cluster of thiazolyl-pyrazolone derivatives through 2, 2 0 -azinobis(3-ethylbenzothiazoline-6-sulphonic acid) (ABTS) radical cation decolorization assay. Compounds 149 and 150 ( Fig.…”
Section: Antioxidant Agentsmentioning
confidence: 99%
“…The antioxidant properties (Table ) of the synthesized nicotinonitrile‐based compounds were screened by using the 2,2′‐azino‐bis(3‐ethylbenzothiazoline‐6‐sulphonic acid) (ABTS) radical cation decolorization assay . The results indicated that clubbing between the nicotinonitrile moiety and thiazole ring in compounds 6a‐c promoted the antioxidant activity to the highest percent inhibition ranged from 82.15% to 86.27%.…”
Section: Resultsmentioning
confidence: 99%
“…Wherever, the π‐electrons are delocalized afterward loss of the proton and the resulted antioxidant values for these derivative have been evaluated. Meanwhile, their reactivity correlates to the substituents type on the ring, and their concentrations to stand on their efficacy and structural activity relationship for these preps derivatives . Moreover, thiazolidinone analogues have a remarkable biological efficacies, such as antioxidant, antitumor, and also antimicrobial activity .…”
Section: Introductionmentioning
confidence: 99%